1970
DOI: 10.1016/0375-9474(70)90417-3
|View full text |Cite
|
Sign up to set email alerts
|

Recoil studies of fission products formed in the fission of 238U by protons of energies 25–85 MeV

Abstract: definite correlati on was observed between the anisotrop y and the depositio n energy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1976
1976
1980
1980

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The most probable charge, Z,, shifts to less neutron-rich nuclides with increasing bombard- uranium showed that E*, leading to products in the symmetric mass region, is not very different than at an energy of 450 MeV. However, in the present energy range, the work of Ramamoorthy et al (18) shows a significant variation in E* of primary fragments in the symmetric mass region as the bombardment energy is increased.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The most probable charge, Z,, shifts to less neutron-rich nuclides with increasing bombard- uranium showed that E*, leading to products in the symmetric mass region, is not very different than at an energy of 450 MeV. However, in the present energy range, the work of Ramamoorthy et al (18) shows a significant variation in E* of primary fragments in the symmetric mass region as the bombardment energy is increased.…”
Section: Discussionmentioning
confidence: 61%
“…The degradation in proton bombardment energy introduced by the target thickness was computed at each energy from the data of Williamson et al (17) and was found to lie within the k 2 MeV spread in the energy of the internal circulating beam of the McGill synchrocyclotron. The target assembly consisted of the following, (i) uranium foil, cleaned with dilute HN03 to remove the oxide coating, subsequently washed with water, acetone, and dried, (ii) high-purity Al catcher foils (front and back) approximately 10 mg cm-2 superficial density, sufficient to stop the recoil of the fission fragments (18,19) and (iii) a Cu monitor coil (99.99% pure) of superficial density 44 mg ~m -~ upstream of the target. Estimates (20,21) of the range of the copper recoil atoms indicate a maximum loss due to recoil of less than 0.003% and thus no catcher foils were used with the monitor foil.…”
Section: Methodsmentioning
confidence: 99%